THE EFFECT OF GARLIC THERAPY ON HYPERTENSION REDUCTION IN THE ELDERLY: A LITERATURE REVIEW - Sri Mumpuni Yuniarsih; Nunung Hasanah; Suherti; Angzilis Sakinah; Rizki Aulia Zahro; Wahyu Dewa Ramadhani; Firkhana Zahrotun Nisa (International Journal of Islamic and Complementary Medicine, 2026)
Hypertension in the elderly increases the risk of cardiovascular disease and reduces quality of life. In addition to pharmacological therapy, garlic (Allium sativum) as a complementary herbal therapy has the potential to lower blood pressure through its allicin and S-allylcysteine ​​content, which act as vasodilators, antioxidants, and angiotensin-converting enzyme inhibitors. This study aims to systematically review the effectiveness of garlic therapy in lowering blood pressure in the elderly with hypertension. The research method used was a literature review with a narrative-descriptive approach. Articles were searched through PubMed, ScienceDirect, Google Scholar, and Scopus databases for publications from 2020 to 2025. A total of 19 articles that met the inclusion criteria were analyzed, including randomized controlled trial designs, quasi-experimental, and pre-experimental. The variables studied included dosage form, dose, duration of administration, changes in systolic and diastolic blood pressure, and side effects. Results showed that various forms of garlic, such as tea, decoction, capsules, black garlic, and aged garlic extract, consistently lowered systolic blood pressure by 10–30 mmHg and diastolic blood pressure by 5–20 mmHg in older adults with hypertension. Reported side effects were generally mild. It was concluded that garlic is potentially effective and safe as a complementary therapy for hypertension in older adults, although further standardized research is needed.